EFEKTIVITAS AUDIT SYARIAH DALAM MENDETEKSI DEVIASI PRODUK KEUANGAN SYARIAH - Umiyati, Umiyati; Febriansyah, Bagas (LPPM - STIE SAKTI ALAM KERINCI, 2024)
This research evaluates the effectiveness of sharia audits in detecting irregularities in sharia financial products, which is important for ensuring compliance with sharia principles such as the prohibition of usury, gharar, and maysir. The research approach used is a combination of qualitative and quantitative. Qualitative data was obtained through in-depth interviews with sharia auditors, management and members of the sharia supervisory board at selected financial institutions. Quantitative data was collected through questionnaires distributed to auditors and management at various sharia financial institutions. Document analysis was carried out on audit reports, financial reports and sharia compliance reports. The instruments used include interview guides, questionnaires, and document checklists. Qualitative data was analyzed using thematic methods, while quantitative data was analyzed using descriptive and inferential statistics. The research results show that the effectiveness of sharia audits is influenced by auditor competence, audit methods, technological support, and management commitment to sharia compliance. Auditors who are knowledgeable in sharia law and accounting are more effective in detecting irregularities, and the use of technology such as audit software and blockchain increases accuracy and efficiency.